Differential expression of DNA fragmentation factor 45 in leukoplakia and oral squamous cell carcinoma and its correlation with TNF-α levels - Sabitha Balakrishnan; Ramya Ramadoss; Rajashree Padmanaban; Rajkumar Krishnan (Oral Oncology Reports)
Background: DNA fragmentation factor (DFF) - 45, a heterodimeric protein, involved in apoptotic processes is found to play important role in various human cancers. Its role in the development and progression of oral cavity squamous cell carcinoma (OSCC) is still unclear. Tumour necrosis factor-α (TNF-α) has been found to be higher in OSCC, yet, the mechanism of circumventing the antitumor effect of this cytokine is not understood. Thus, the aim of this study was to evaluate the expression of DFF-45 in samples of OSCC, leukoplakia, and healthy oral mucosa (control) and correlate it with salivary and serum TNF-α. Materials and methods: Surgically excised specimens from patients with primary OSCC (n = 20) leukoplakia (n = 30) and normal oral mucosa (n = 25) were immuno stained for DFF-45. The relationship of DFF-45expression with clinical parameters and histological grading was also evaluated. TNF-α levels were measured in serum and saliva collected from study subjects using cytokine ELISA technique. Results: The expression of DFF-45 in OSCC was either absent or mild, while a significantly up-regulated expression of this protein was observed in leukoplakia lesions. TNF-α levels in both saliva and serum were significantly higher in OSCC group compared to control and leukoplakia. We observed a negative correlation between TNF-α levels and DFF-45 expression in OSCC, similar observation was found with histological staging of OSCC. Conclusion: The absence of DFF-45 in oral cancer lesion suggests that this protein may suppress tumour progression. Down regulation of DFF-45 by tumor cells may be a mechanism to evade the anti-cancer effect of TNF-α and further investigations may unravel its role into malignant transition.